2020
DOI: 10.1186/s12986-020-00477-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-arginine and low-protein diets induce hepatic lipid accumulation through different mechanisms in growing rats

Abstract: Background: Dietary protein deficiency and amino acid imbalance cause hepatic fat accumulation. We previously demonstrated that only arginine deficiency or total amino acid deficiency in a diet caused significant hepatic triglyceride (TG) accumulation in young Wistar rats. In this study, we explored the mechanisms of fatty liver formation in these models. Methods: We fed 6-week-old male Wistar rats a control diet (containing an amino acid mixture equivalent to 15% protein), a low-total-amino acid diet (equival… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…In the past few years, many studies have found that protein restriction is a promising nutritional strategy that can adjust the balance between resources, environment, and biological metabolism, thereby affecting the energy status and lipogenic-related genes. However, protein restriction has been reported to produce higher fat content and subcutaneous fat thickness, thereby enhancing lipid accumulation. , In this study, the effects and potential mechanism of five treatments, a positive control (16% CP), a negative control (12% CP), and three protein-restricted diets (12% CP) supplemented to three varying BCAA ratios (Leu/Ile/Val = 2:1:1, 2:2:1, and 2:1:2) on lipid metabolism in the finishing pig model, which is the most important time for fat deposition, were further investigated. Consistent with previous research, our results showed that supplementation of BCAAs during the fat deposition phase could ameliorate the poor performance, especially in lipid metabolism, caused by protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, many studies have found that protein restriction is a promising nutritional strategy that can adjust the balance between resources, environment, and biological metabolism, thereby affecting the energy status and lipogenic-related genes. However, protein restriction has been reported to produce higher fat content and subcutaneous fat thickness, thereby enhancing lipid accumulation. , In this study, the effects and potential mechanism of five treatments, a positive control (16% CP), a negative control (12% CP), and three protein-restricted diets (12% CP) supplemented to three varying BCAA ratios (Leu/Ile/Val = 2:1:1, 2:2:1, and 2:1:2) on lipid metabolism in the finishing pig model, which is the most important time for fat deposition, were further investigated. Consistent with previous research, our results showed that supplementation of BCAAs during the fat deposition phase could ameliorate the poor performance, especially in lipid metabolism, caused by protein restriction.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the protein source substitution might cause more lipid accumulation in visceral organs instead of muscle. In mammals, it has been reported that dietary amino acid imbalance and dietary protein malnutrition both induces fat deposition in the liver ( Otani et al., 2020 ), suggesting that amino acid imbanlance or decreased protein digestibility in YM substitution groups may disturb the lipid metabolism in fish.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term intake of low protein but not high protein resulted in hepatic lipid accumulation and hepatocellular swelling, which was consistent with previous findings. 6,32,33 The detrimental effects of low protein on lipid homeostasis might be in part mediated by several pathways such as enhanced Srebp-1c and Acc involving lipogenesis, upregulation of Lpl-related fat uptake, and down-regulation of Mttp-related lipoprotein secretion. 19,32,33 Importantly, we found that the IHL diet caused lipid accumulation, whereas the ILH diet restored liver lipid homeostasis with a one-week intake of high casein or pork protein diets.…”
Section: ■ Discussionmentioning
confidence: 99%
“…6,32,33 The detrimental effects of low protein on lipid homeostasis might be in part mediated by several pathways such as enhanced Srebp-1c and Acc involving lipogenesis, upregulation of Lpl-related fat uptake, and down-regulation of Mttp-related lipoprotein secretion. 19,32,33 Importantly, we found that the IHL diet caused lipid accumulation, whereas the ILH diet restored liver lipid homeostasis with a one-week intake of high casein or pork protein diets. Overall, these results suggested that hepatic lipid accumulation rapidly responded to the dietary protein change within one week, belonging to a fast reaction.…”
Section: ■ Discussionmentioning
confidence: 99%